Interplay between Host tRNAs and HIV-1: A Structural Perspective - Jinwei Zhang (Viruses, 2021)
The cellular metabolism of host tRNAs and life cycle of HIV-1 cross paths at several key virus–host interfaces. Emerging data suggest a multi-faceted interplay between host tRNAs and HIV-1 that plays essential roles, both structural and regulatory, in viral genome replication, genome packaging, and virion biogenesis. HIV-1 not only hijacks host tRNAs and transforms them into obligatory reverse transcription primers but further commandeers tRNAs to regulate the localization of its major structural protein, Gag, via a specific interface. This review highlights recent advances in understanding tRNA–HIV-1 interactions, primarily from a structural perspective, which start to elucidate their underlying molecular mechanisms, intrinsic specificities, and biological significances. Such understanding may provide new avenues toward developing HIV/AIDS treatments and therapeutics including small molecules and RNA biologics that target these host–virus interfaces.